Rising incidence of recreational ketamine use: Clinical cases and management in emergency settings - Sabrina Marongiu; Maarten van Eijk; Femke M.J. Gresnigt; Esther A. Croes; Eric J.F. Franssen (Toxicology Reports)
The recreational use of ketamine has risen significantly in the Netherlands, particularly among young adults in nightlife settings. This trend has been accompanied by an increase in first aid incidents involving ketamine, often in combination with other substances such as alcohol or MDMA, leading to heightened toxicity. Acute intoxication with ketamine manifests through symptoms like agitation, hallucinations, nausea, tachycardia, and hypertension, while frequent use is associated with long-term complications, including ketamine-induced uropathy. Although ketamine is not currently included in standard toxicological screenings, its detection can aid in diagnosing mixed intoxications, excluding alternative causes, and facilitating referral to follow-up care. Routine inclusion of ketamine in toxicological screening could improve diagnostic precision and better address the health risks associated with its growing prevalence.